The Effect of The Blended Learning Model Assisted by The Google Classroom Application on The Science Learning Outcomes - Islamiyati, Dian; Bahtiar, Bahtiar; Zohri, Muhammad (Indonesian Publication Center, 2022)
This study aims to examine the effect of the blended learning model assisted by Google Classroom on students’ science learning outcomes. The research employed a quasi-experimental design with a pretest-posttest control group. The sample consisted of 31 students in the experimental class and 30 students in the control class, selected using simple random sampling. Data were collected using a multiple-choice test. The results showed that the average post-test score of the experimental class (86.58) was higher than that of the control class (65.20). Hypothesis testing using an independent t-test indicated that tcount (10.36) > ttable (2.00) at a 5% significance level. These findings indicate that the blended learning model assisted by Google Classroom has a significant effect on students’ science learning outcomes. These findings indicate that the blended learning model assisted by Google Classroom is effective in improving students’ science learning outcomes.